Molecular and physiological mechanisms underlying magnesium-deficiency-induced enlargement, cracking and lignification of Citrus sinensis leaf veins. (27th April 2020) - Ye, Xin; Chen, Xu-Feng; Cai, Li-Ya; Lai, Ning-Wei; Deng, Chong-Ling; Guo, Jiu-Xin; Yang, Lin-Tong; Chen, Li-Song
Abstract: Little is known about the physiological and molecular mechanisms underlying magnesium (Mg)-deficiency-induced enlargement, cracking and lignification of midribs and main lateral veins of Citrus leaves. Citrus sinensis (L.) Osbeck seedlings were irrigated with nutrient solution at a concentration of 0 (Mg-deficiency) or 2 (Mg-sufficiency) mM Mg(NO3 )2 for 16 weeks. Enlargement, cracking and lignification of veins occurred only in lower leaves, but not in upper leaves. Total soluble sugars (glucose + fructose + sucrose), starch and cellulose concentrations were less in Mg-deficiency veins of lower leaves (MDVLL) than those in Mg-sufficiency veins of lower leaves (MSVLL), but lignin concentration was higher in MDVLL than that in MSVLL. However, all four parameters were similar between Mg-deficiency veins of upper leaves (MDVUL) and Mg-sufficiency veins of upper leaves (MSVUL). Using label-free, liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, we identified 1229 and 492 differentially abundant proteins (DAPs) in MDVLL vs MSVLL and MDVUL vs MSVUL, respectively. Magnesium-deficiency-induced alterations of Mg, nonstructural carbohydrates, cell wall components, and protein profiles were greater in veins of lower leaves than those in veins of upper leaves. The increased concentration of lignin in MDVLL vs MSVLL might be caused by the following factors: (i) repression of cellulose and starch accumulation promoted lignin biosynthesis; (ii) abundances of proteins involved in phenylpropanoid biosynthesis pathway, hormone biosynthesis and glutathione metabolism were increased; and (iii) the abundances of the other DAPs [viz., copper/zinc-superoxide dismutase, ascorbate oxidase (AO) and ABC transporters] involved in lignin biosynthesis were elevated. Also, the abundances of several proteins involved in cell wall metabolism (viz., expansins, Rho GTPase-activating protein gacA, AO, monocopper oxidase-like protein and xyloglucan endotransglucosylase/hydrolase) were increased in MDVLL vs MSVLL, which might be responsible for the enlargement and cracking of leaf veins.